2020
DOI: 10.1186/s13063-020-4134-5
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis Information and Education: a randomised, controlled feasibility trial

Abstract: Background: There has been comparatively little patient information about bronchiectasis, a chronic lung disease with rising prevalence. Patients want more information, which could improve their understanding and selfmanagement. A novel information resource meeting identified needs has been co-developed in prior work. We sought to establish the feasibility of conducting a multi-centre randomised controlled trial to determine effect of the information resource on understanding, self-management and health outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…There were studies that could have further refined the programme theories but were excluded due to ineligibility. Noteworthy studies that were omitted included one multi-faceted qualitative study [55] that explored the factors that influenced adherence to self-management strategies and three studies that only evaluated a single intervention [54,56,57]. The overall findings should be viewed as provisional and non-exhaustive due to limited iterative searching resulting from a lack of resources.…”
Section: Methodological Limitations and Implications For Further Researchmentioning
confidence: 99%
“…There were studies that could have further refined the programme theories but were excluded due to ineligibility. Noteworthy studies that were omitted included one multi-faceted qualitative study [55] that explored the factors that influenced adherence to self-management strategies and three studies that only evaluated a single intervention [54,56,57]. The overall findings should be viewed as provisional and non-exhaustive due to limited iterative searching resulting from a lack of resources.…”
Section: Methodological Limitations and Implications For Further Researchmentioning
confidence: 99%
“…Feasibility and high demand for online access to a web-based bronchiectasis information resource has been demonstrated, but this is yet to be proven in a full clinical trial. 28 The UK Government's digital inclusion strategy identified key barriers including age and social deprivation, that should be considered in design of self-management programmes. 29 Availability of resources was a key factor with a scarcity of high-quality information and evidence of a 'make do' culture.…”
Section: Structure Delivery and Resourcesmentioning
confidence: 99%
“…Specifically, participants in these studies were provided with a technology platform to access information and activities that develop new knowledge, skills, and attitudes for self-management of chronic respiratory disease (Table 1). The platforms have multiple forms, i.e., websites [5][6][7][8][9][10][11], apps [12][13][14], "serious games" [15], or virtual reality environments [16], incorporating activities for learning information and skills that can be applied to managing their condition.…”
Section: Impact Of Technology-enabled Patient Educationmentioning
confidence: 99%
“…For all studies that measured patient satisfaction, technology-enabled patient education was a positive experience by the majority of participants. The majority of participants would recommend the technology-enabled patient education to peers, finding the webbased and application-based education kept them motivated, was easy to use, and was relevant and perceived their knowledge and skills to have improved [5,6,9,12,[14][15][16]21,23]. Participants also found that the technology solution meant the information was always readily available and not able to be misplaced, and this was very helpful [6].…”
Section: User Satisfaction With Technology-enabled Patient Educationmentioning
confidence: 99%